An SMS Based Push Email Server - Omotunde, Ayokunle Ayobami; Izang, Aaron Afan; Kuyoro, Shade; Abel, Samuel B; Mensah, Yaw (Discoveries in Agriculture and Food Sciences, 2015)
The communication industry is ever evolving with new media of communicating between people and these various media have made it impossible to determine the best means of communication. This work in its entirety aims at reducing the stress and vigour that sometimes accompany some of the different means of communication. The email has proven to be one of the most used means of online communication. However, a major drawback of email communication is that for a mailbox to be accessed, it requires an active and working internet connection which is often times expensive and cannot be afforded continuously by an average individual. This work was created to eliminate such factor when it comes to using the email as a means of communication by assisting the e-mail account owner to forward his newly received mail by SMS to the user’s mobile phone with or without internet access on the mobile device.